1986
DOI: 10.1002/jbm.820200214
|View full text |Cite
|
Sign up to set email alerts
|

Composites for use in posterior teeth: Mechanical properties tested under dry and wet conditions

Abstract: The purpose of this investigation was to determine some mechanical properties of eight different posterior composites, and how they are affected by water sorption. Creep characteristics in compression were expressed as compliance/log time functions. Stress-strain relationship at a constant loading rate was determined both in compression and flexure, and presented as elastic modulus, ultimate strength, and ultimate strain. Water sorption increased creep values for all materials. Generally, the materials with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
9

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 18 publications
2
58
0
9
Order By: Relevance
“…Previousstudieshavewidelyreportedthatwaterhad the effect of reducing the surface hardness of MBCs 7,21) . As for the water sorption and water solubilityofdentalRBCmaterials,theydependona hostoffactors:chemistryofthemonomerresins,the extent of polymerization of the polymer matrix 22) , filler particle size, shape, and distribution 23,24) , and the interfacial properties between the filler and resin matrix 25,26) . In this study, a significant softening of MBCs (Filtek P60, Z250, and Supreme XT) was observed after conditioning in water when compared withthecontrolgroups.TheMBCsanalyzedinthis study had the same polymer matrix composition (comprising Bis-GMA, Bis-EMA, UDMA, and TEGDMA).…”
Section: Discussionmentioning
confidence: 99%
“…Previousstudieshavewidelyreportedthatwaterhad the effect of reducing the surface hardness of MBCs 7,21) . As for the water sorption and water solubilityofdentalRBCmaterials,theydependona hostoffactors:chemistryofthemonomerresins,the extent of polymerization of the polymer matrix 22) , filler particle size, shape, and distribution 23,24) , and the interfacial properties between the filler and resin matrix 25,26) . In this study, a significant softening of MBCs (Filtek P60, Z250, and Supreme XT) was observed after conditioning in water when compared withthecontrolgroups.TheMBCsanalyzedinthis study had the same polymer matrix composition (comprising Bis-GMA, Bis-EMA, UDMA, and TEGDMA).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used diluent is triethyleneglycol dimethacrylate (TEGDMA). Despite of being considered highly stable structures, dental composites are susceptible to degradation (Geurtsen, 1998) due to the incomplete polymerization and the influence of the aqueous oral environment (Oysaed and Ruyter, 1986). When a composite material is immersed in water, some of the components, such as unreacted monomers (Inoue and Hayashi, 1982;Oysaed et al, 1988;Tanaka et al, 1991;Ferracane, 1994;Örtengren et al, 2001), filler particles (Söderholm, 1983) and other components (Lygre et al, 1999) are leached out of the material.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Buna ek olarak siman tabakasının kalınlığının artması, simanın su absorpsiyon miktarının artmasına neden olabilir. 18,19 Kalın bir rezin siman tabakası kullanıldığında su depolaması ile gerçekleşen yaşlanma, cam porselenlerin dayanıklılığını azaltmaktadır. 18 Kenar ve iç yüzey uyumun değerlendirilmesi amacıyla yapılan birçok çalışmada ölçüm noktalarının sayısı konusunda, literatürde ortaya konan herhangi bir standart bulunmamaktadır.…”
Section: Discussionunclassified
“…YÜCE, TÜRK J Dent Fac Atatürk Uni Cilt:27, Sayı:1, Yıl: 2017, Sayfa, [19][20][21][22][23][24][25][26] Çalışmamızda venerin iç yüzeyi ile preparasyonun aksiyal duvarı arasındaki dikey yöndeki ölçüm iç yüzey aralık, aynı ölçümün kenarda uygulanması ise kenar aralık olarak tanımlanmaktadır. Kenarda dikey yöndeki aralığın öneminin yanı sıra, yatay yöndeki mesafe ise periodontal hastalıklar ile yakından ilişkili olarak restorasyonun taşkınlık miktarını ortaya koymaktadır.…”
Section: Discussionunclassified